Flight control law of unmanned aerial vehicles based on robust servo linear quadratic regulator and Kalman filtering. (5th January 2017) - Zhi, Yongfeng; Li, Gaoshang; Song, Qun; Yu, Ke; Zhang, Jun
A new flight control law for unmanned aerial vehicles based on robust servo linear quadratic regulator control and Kalman filtering is proposed. This flight control law has a simple structure with high dependability in engineering. The pitch angle controller, which is designed based on the robust servo linear quadratic regulator control, is given to show the flight control law. Simulation results show that the pitch angle controller works well under noise-free conditions. Finally, Kalman filtering is applied to the pitch angle controller under noisy conditions, and the simulation results show that the proposed method reduces the influence of noise.